Labor Taxes and Wages: Evidence from Italy - Giorgio Brunello; Maria Laura Parisi; Daniela Sonedda (Center for Economic Studies and ifo Institute (CESifo), 2002)
We study the empirical relationship between labor taxation and pretax wages in Italy. We find that higher tax progressivity increases pretax wages. To explain this result, we introduce in an informal way a relative wage effect and argue that the combination of this effect with the labor supply effect dominates the wage moderation effect. We find also evidence that changes in payroll taxes are not fully absorbed by offsetting changes in the pretax wage and affect labor costs and employment. The evidence on the effect of the average income tax rate on pretax wages is more mixed, but it also points to the presence of some degree of real wage resistance. Finally, we find significant differences in the relationship between labor taxes and pretax wages by age group but not by skill or region of residence.
Keywords: 330; progressive taxation; wage determination; Italy